IDENTIFICATION OF KAWI-SONGGORITI GEOTHERMAL PROSPECTS BASED ON FAULT AND FRACTURE DENSITY (FFD) - Nur Aini Gama Lestari; Sukir Maryanto; Didik Rahadi Santoso (Journal of Environmental Engineering and Sustainable Technology, 2020)
The aim of this research is to identify the surface structures of geothermal area in Kawi-Songgoriti based on lineament density and surface manifestation. The lineament density is processed by using satellite image as the input data. The surface structures were analyzed through the density of lineaments on the surface with FFD method. The lineaments are assumed associated with fractures or faults found in geothermal areas those are generally covered by surface manifestation which are hard to be identified. These faults and fractures were assumed as weak line that act as fluid thermal movement, thereby it can be used as guidance for the location of permeable area or a reservoir.  As a result, the high lineament density can be found in Kawi thus assumed as the control of Songgoriti manifestation.